Family Caregiver Perspectives on Caring for Ventilator-Assisted Individuals at Home - Rachael Evans; Michael Catapano; Dina Brooks; Roger Goldstein; Monica Avendano (Canadian Respiratory Journal)
BACKGROUND: The trend of patients who are invasively ventilated to prefer home care is one that benefits both the patient and the health care system. However, this assumes a role for patients’ family members to become informal caregivers.